ANALISIS PENERAPAN NILAI KEARIFAN LOKAL RUMAH BETANG DAYAK IBAN DI SUNGAI UTIK KECAMATAN EMBALOH HULU - Febridika Lenzenzia Lily; Yohanes Bahari; Rustiyarso Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract Analysis of the Application of the Local Wisdom Value of Betak Dayak Iban River House Utik, Embaloh Hulu District. The general problem of this research is how the application of the local wisdom values of the Dayak Iban betang house Sungai Utik, Embaloh Hulu District. With sub-problems (1) how to apply the value of the solidarity of Iban Sui Utik Dayak betang house. (2) How is the value of Dayban Iban Sui Utik's mutual cooperation. This study aims to find out the application of local wisdom value in Betang Sungai Utik home, Embaloh Hulu District. The research method used is descriptive with a form of qualitative research. Data sources of this research are community leaders and Betang community and the data are interview sheets with community leaders. Data collection techniques in research using direct observation techniques, direct interviews and documentation. The results of this study indicate that the application of the value of local wisdom continues to be carried out in the life of the Dayak Iban community in the Betang Sungai Utik house. This shows that the era of globalization like the current Dayak Iban community still applies the values of local wisdom. Because local wisdom is a hereditary inherited value from ancestors. Keywords: Dayak Iban, Local Wisdom, Value